Peningkatan Rock Painting terhadap Kecerdasan Visual Spasial Anak di RA Darul Fikri - Novita Rizki, Silfia; Kustiawan, Usep; Suryadi, Suryadi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
This study aims to improve spatial visual intelligence through rock painting techniques at RA Darul Fikri. This study uses a classroom action research design (CAR) with a collaborative model because in its implementation there is collaboration between researchers and teachers. The teacher plays a role in implementing the activity design that the researcher has designed, and helps all the preparations for the researcher. The success or failure of a cycle is based on the achievement of predetermined success indicators. Broadly speaking, there are four stages that are passed, namely: 1) planning, 2) implementing the action, 3) observing, and 4) reflection. Cycle I has only 39% class development achievements, then it is carried out again in cycle II with 61% class development results, and refers to the shortcomings of cycle II done again in cycle III with class development achievements of 87%. Rock painting technique is expected to be used by various institutions to improve children's spatial visual intelligence and to be one of the solutions in increasing children's spatial visual intelligence. It is hoped that future researchers can examine in detail and have a better cycle and do not limit the time used. Then for the next researcher using a different institution.